2017
DOI: 10.4038/sljog.v39i4.7825
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Cytomegalovirus Infection During Pregnancy in a Teaching Hospital, Western province, Sri Lanka

Abstract: Primary Cytomegalovirus (CMV) infection during pregnancy is a serious threat to the fetus. Although vertical transmission is likely to occur as a result of maternal infection, the rate of permanent sequelae is higher among infants born to mothers with primary CMV infection. Diagnosis of CMV infection among healthy adults generally relies on serological testing as most of them are asymptomatic. CMV infection in pregnancy is barely studied in Sri Lanka. This study aims in screening for CMV infection of selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Majority of our sample have not received adjuvant steroids which have shown to improve jaundice clearance [12,13]. Studies have shown in CMV -associated biliary atresia COJ can be as low as 15% [14] .Exact prevalence of congenital CMV infection in Sri Lanka is not known but postulated to be much higher than in western countries [15]. We have made an observation that many episodes of cholangitis going undetected in early postoperative period under the umbrella term "Post-op fever" without prompt and aggressive antibiotic treatment.…”
Section: Resultsmentioning
confidence: 95%
“…Majority of our sample have not received adjuvant steroids which have shown to improve jaundice clearance [12,13]. Studies have shown in CMV -associated biliary atresia COJ can be as low as 15% [14] .Exact prevalence of congenital CMV infection in Sri Lanka is not known but postulated to be much higher than in western countries [15]. We have made an observation that many episodes of cholangitis going undetected in early postoperative period under the umbrella term "Post-op fever" without prompt and aggressive antibiotic treatment.…”
Section: Resultsmentioning
confidence: 95%